Steps to a nuclear-free world, Brussels - Moscow 12 January - 12 October 1995 (Amsterdam: LAKA Foundation; Berchem: De Wrikker, 1995)
"For Mother Earth ; writing, editing and lay-out: LAKA Foundation"